PENGARUH KEPEMIMPINAN DAN KOMPETENSI TERHADAP PRESTASI KERJA MELALUI MOTIVASI KERJA DILINGKUNGAN SDN 005 SEKUPANG - firdiyansyah, Indra indra (Jurnal Ipteks Terapan, 2015)
This research examined the influence between leadership style to motivation, competency to motivation, motivation to performance and also examined the influence between leadership and competency to performance with motivation as intervening variable. Once the data is obtained, then the data were analyzed using path analysis . The test results indicate that the structural model of the first, direct leadership and significant effect on job motivation. In the second structural model, direct leadership,competence, and motivation have a significant effect on job performance and indirectly through work motivation, leadership and competence both significant effect on job performance leadership over where variables have a significant effect in improving job performance, either directly or indirectly. The third contribution of exogenous variables, namely leadership, competence and motivation on work performance by 76.8 % while the remaining 23.2 % was contributed by other factors outside of our model.The conclusion of this study is the need for a more active role of the principal to increase work performance of teachers